Is Dyslipidemia a Risk Factor for Trastuzumab-induced Cardiotoxicity in Breast Cancer Patients? A Systematic Review and Meta-Analysis - Jaime Francisco Pires Pinho (2021)
Background: Breast cancer patients undergoing trastuzumab treatment have greater risk of cardiovascular disease. Several risk factors for this effect have been proposed. However, the role of dyslipidemia is not completely known. This PRISMA-guided systematic review and meta-analysis aimed to explore the role of dyslipidemia as a risk factor for trastuzumab-induced cardiotoxicity and quantify its impact. Methods: The investigators searched MEDLINE, Scopus, and Web of Science up to 25th October 2020. A random-effects model was used to determine pooled estimates of the results. The primary endpoint was trastuzumab-induced cardiotoxicity in patients with and without dyslipidemia. Results: 39 studies were selected for inclusion in our systematic review assessing a total of 21079 patients. Diagnostic criteria for dyslipidemia and classification of cardiotoxicity differed greatly between studies. One study demonstrated a statistically association between dyslipidemia and cardiotoxicity (OR=2.28, 95% confidence interval =1.22-4.26, p=0.01). In all other studies, such association was not observed. 21 observational studies were eligible for our meta-analysis including a total of 6135 patients. In this meta-analysis of largely unadjusted data, dyslipidemia was significantly associated with cardiotoxicity following treatment with trastuzumab (OR = 1.25, 95% CI = 1.01-1.53, p=0.04, I² = 0%). however, subgroup analysis of studies reporting adjusted measures did not demonstrate a significant association (OR= 0.89, 95% CI = 0.73-1.10, p=0.28, I2=0%). Conclusion: This systematic review and meta-analysis did not demonstrate a significant association between dyslipidemia alone and the development of cardiotoxicity. In the absence of other relevant cardiovascular risk factors, routine review of the lipid profile in these patients might not be obligatory and management could be performed without referral for cardio-oncology evaluation. Further investigation on cardiovascular risk factors for trastuzumab-induced cardiotoxicity is required to confirm these results.